2021
DOI: 10.1155/2021/6635836
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] The Role of Posttranslational Modification and Mitochondrial Quality Control in Cardiovascular Diseases

Abstract: Cardiovascular disease (CVD) is the leading cause of death in the world. The mechanism behind CVDs has been studied for decades; however, the pathogenesis is still controversial. Mitochondrial homeostasis plays an essential role in maintaining the normal function of the cardiovascular system. The alterations of any protein function in mitochondria may induce abnormal mitochondrial quality control and unexpected mitochondrial dysfunction, leading to CVDs. Posttranslational modifications (PTMs) affect protein fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 152 publications
0
7
0
Order By: Relevance
“…Among twenty AAs, modifications are deposited mainly on a lysine residue, the only AA with a side chain amine, which can be covalently modified by glycosyl, propionyl, butyryl, acetyl, hydroxy, crotonyl, ubiquitin and ubiquitin-like groups. Ubiquitination is vital for myocardial ischemia/reperfusion (I/R) injury, cardiomyopathy, and heart failure ( 23 ). It has been reported that parkin, cooperating with the ubiquitin-conjugating enzyme UbcH7, functions as a ubiquitin ligase to promote protein degradation ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among twenty AAs, modifications are deposited mainly on a lysine residue, the only AA with a side chain amine, which can be covalently modified by glycosyl, propionyl, butyryl, acetyl, hydroxy, crotonyl, ubiquitin and ubiquitin-like groups. Ubiquitination is vital for myocardial ischemia/reperfusion (I/R) injury, cardiomyopathy, and heart failure ( 23 ). It has been reported that parkin, cooperating with the ubiquitin-conjugating enzyme UbcH7, functions as a ubiquitin ligase to promote protein degradation ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Amongst PTMs, peptide oxidation [ 53 ], phosphorylation [ 54 , 55 ], and citrullination [ 56 ] have the potential to generate unique pools of antigens shared by cells with similar metabolic alterations. Post-translational modifications of proteins may also impact mitochondrial dynamics, protein quality control, and, ultimately, mitochondrial performance [ 57 ]. SUMOylation, S-oxidation (sulfinylation and sulfenylation), S-glutathionylation, S-nitrosylation, acetylation, phosphorylation, glycosylation, protein cleavage, crotonylation, ubiquitination, and ADP-ribosylation are PTMs reported in the mitoproteome [ 57 , 58 ].…”
Section: Post-translational Modifications: a Different Way To Generat...mentioning
confidence: 99%
“…Post-translational modifications of proteins may also impact mitochondrial dynamics, protein quality control, and, ultimately, mitochondrial performance [ 57 ]. SUMOylation, S-oxidation (sulfinylation and sulfenylation), S-glutathionylation, S-nitrosylation, acetylation, phosphorylation, glycosylation, protein cleavage, crotonylation, ubiquitination, and ADP-ribosylation are PTMs reported in the mitoproteome [ 57 , 58 ]. All these PTMs generate new antigens independently of their encoding genes, and in several instances these modifications promote MHC binding and TCR/MHC interactions.…”
Section: Post-translational Modifications: a Different Way To Generat...mentioning
confidence: 99%
“…The binding of these UBL proteins to target proteins is also dependent on the level of E1 activating enzymes, E2 binding enzymes, and E3 ligases. The PTM function of UBL proteins is implicated in the nervous system [ 6 ], endocrine system [ 6 ], cardiovascular system [ 7 ], and many other diseases. Currently, the role of UBL modification in tumor occurrence and development is receiving a lot of attention [ 8 , 9 , 10 ] ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%